A morphometric study of the restinga ecotype of Anacardium occidentale (Anacardiaceae): wild coastal cashew populations from Piauí, Northeast Brazil. Issue 2 (24th February 2019) - de Andrade, Ivanilza Moreira; de Oliveira Nascimento, Joana D'Arc; de Sousa, Márcia Vieira; dos Santos, Juelina Oliveira; Mayo, Simon Joseph
Abstract : The infraspecific taxonomy of wild Anacardium occidentale is little studied. We investigated whether wild populations on coastal dunes in Piauí, Brazil differed from non‐wild populations. Ten populations were sampled and twenty one morphological variables were measured. Variation within and between populations was investigated with univariate and multivariate statistics. Dune populations were mostly more similar to one another than to domesticated ones. There was significant correlation between inter‐population geographical distance and morphological dissimilarity. Classification methods showed 96.4% successful assignment to the dune category and 86% to 100% to dune populations individually, but dune and non‐dune populations overlap morphologically. Dune populations had shorter, broader leaves, shorter drupes and fewer secondary veins. Non‐dune coastal populations showed strongest similarity to dune populations. Populations distant from the coast were most divergent. The population from the cerrado region was most distinct, with thicker leaf blades and narrower petioles. The dune populations are recognised as the "restinga ecotype" of A. occidentale . Correlation of dissimilarity and distance may result from gene flow and/or non‐inherited environmental effects. Ecology and nomenclature (including the vernacular "cajuí") of the restinga ecotype are reviewed. Further comparison of restinga populations is needed along the Brazilian coastline and with natural cerrado populations.